Stakeholder’s Perception of Participation in Community Forest Program in Sigi Regency - Ferianto, Fiki; Hidayat, Rahmat (Journal of Public Administration and Government, 2026)
Efforts to preserve forests while improving community welfare have been undertaken by the Government through the Social Forestry Program. Community Forestry (Hutan Kemasyarakatan, or HKm) is one of the schemes established under this program. HKm is considered a breakthrough in increasing community participation in forest management. However, this view has also faced challenges from various parties, as the participation carried out so far has been superficial. This study aims to identify and explore the tendencies of actors' perceptions regarding participation in HKm and its influence on program realization and inter-actor relationships. The method used is descriptive qualitative, with data collected through observation, documentation, and in-depth interviews. This study finds that all stakeholders consider public participation in the HKm program important. However, Village Governments and Field Facilitators argue that the level of public involvement is highly influenced by the human resource capacity and personal orientation of the field implementers themselves.